Changes in Agri-Business Outcomes among the Dairy Beneficiaries of Contracted Extension Service Delivery Model in Kenya - Bockline Omedo Bebe; John Gowland Mwangi; Nicholas Ozor (Journal of Agricultural Extension, 2016)
This study compared changes in uptake of agri-business practices, productivity and wealth creation between dairy beneficiaries and non-beneficiaries of Contracted Extension Service Delivery Model (CESDM) implemented by Kenya Agricultural Productivity and Agribusiness Project (KAPAP) in selected counties of Kenya since 2010. Results showed a large increase in the proportion of beneficiaries accessing extension services from private service providers and expressing satisfaction with CESDM, attaining higher dairy productivity in milk and in gross margins per animal per year. However, there was only a marginal increase in willingness to pay or paying for the services and majority of beneficiaries continued to sell milk through informal market outlets. On aggregate, CESDM posted positive net benefits and multiplicative economic power with the best performing dairy chains multiplying every shilling invested 4 to 46 times. On average, beneficiaries earned KES 4993 per farmer at a cost of KES 353 for services, inputs and equipment. We conclude that CESDM can be a viable and rewarding approach for delivering extension services to smallholder farmers but it is necessary to strengthen farmer cooperative societies because those paying for private services are still too few to sustain remunerative private sector investment in extension service delivery.Â